URGENSI PENERBITAN PETUNJUK TEKNIS PEMASANGAN ALAT PENDETEKSI ELEKTRONIK BAGI MANTAN NARAPIDANA KEKERASAN SEKSUAL ANAK - Siti Zahra Alifah Saesara, (2023)
The number of sexual violence against children continues to increase every year. This is a serious problem for the Indonesian government because the constitution has mandated it to provide protection for children. Various efforts have been made by the Government of Indonesia to impose sanctions on the installation of electronic detection devices, including former sexual violence against children. However, until now there has been no derivative rule in the form of technical instructions in the form of a Ministerial Regulation to provide a more comprehensive regulation regarding the installation of a quo electronic detection devices. The purpose of the study was to determine the urgency of installing electronic detection devices for sexual violence and to review technical instructions for the installation of electronic detection devices for former violence in the future. This research method uses normative research. The data sources in this study used secondary data sources consisting of primary, secondary, and tertiary legal materials. This study uses a legal and conceptual approach. The data analysis technique uses qualitative, descriptive, analytical, and prescriptive data presentation techniques. Based on the results of the study, the installation of electronic detection devices for former child sexual abuse is very important. Because, sexual violence against children is rife, the act of installing electronic detection devices is similar to the principles of the double track system in criminal law, there is legal certainty in terms of the act of installing electronic detection devices, so that sexual violence can be carried out after serving the main crime and anticipating the occurrence of recidivism. . Formulation of instructions for the implementation of the act of installing electronic detection devices for former violence against children in the future comprehensively on the part of those who carry out preparation, implementation, supervision, selection of forms, to electronic detection devices. In addition, there is a need for reformulation of Article 81 paragraph (7) which is the basis of Article 81 protection/alternatives.